Pre-Menopause and Herbal Therapies - Olumide I, Ogunyemi,; Ifeanyi O, Amaechina,; Olubunmi, A, Eruola,; Mercy A, Ogunbisi,; Olujide H, Adebiaye,; Samson A., Omogbehin, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Menopause happens because the ovaries stop producing the hormones – estrogen and progesterone. Sufferers of early menopause can regain the potency of their ovaries through Herbal therapies. The use of herbs as medication for the treatment of diverse of illness and/or diseases had long been in practice before our common era. In this study, eleven local herbs whose concoctions have been reported help to prolong and suppress premature menopause and its characterized symptoms were identified and analysed to know the biological active chemical substances that perform the elixir of ovarian dysfunctions in women. The herbs are: Tinospora cordifolia, Zanthoxylum zanthoxyloides, Chrysophyllum albidum, Citrullus lanatus, Adenopus breviflorous, Momordica charantia, Anthocleista djaonensis, Strophantus hispidus, Securidaca logipendiculata, Alchornea cordifolia and N. latifolia. The milled powders were de-fated by soxhlet extraction. The extract was analysed with GC-Agilent Technologies 6890N cum with MS –Agilent Tech 5975C series for elucidation of chemical composition and structures present in the extract. To achieve this, automatic injector Agilent technologies 7683B series with column HP-5-MS were used. Analysis showed the following biological active chemical substances of which many are alkaloids and lipids, phenolic compounds etc. Some of these compounds and their uses have been reported in literatures.